The Implementation of Cooperative Problem-Solving Rubric Towards Turkish Fourth Grade Students - Gülçin Karakus; Gürbüz Ocak (Mimbar Sekolah Dasar, 2022)
This study aimed to develop an analytical rubric for teachers to observe and evaluate students’ performance in showcasing the cooperative problem-solving process. Thus, a rubric was prepared. Angles to evaluate the student performance were included and a quad rank scale was used in the rubric. Dimensions used in the rubric were based on the PISA 2015 cooperative problem-solving dimensions. The weighted kappa coefficient was calculated for reliability. The validity of the rubric was provided by taking into the opinions of experts. The dimensions used were; common understanding, communication, respect, solving problems together, discussion, and finding common solutions. The weighted kappa coefficient of the rubric was 660 on common understanding; 644 on communication; 835 on respect; 829 on solving problems together; 825 on discussion, and 822 on finding common solutions. Additionally, the rubric was validated by controlling the content, structure, and validity criteria. The results showed that the cooperative problem-solving rubric was reliable and valid to evaluate cooperative problem-solving skills. The rubric presented a comprehensive assessment and scoring for cooperative problem-solving skills.